Effects of buprenorphine, methadone, and cariprazine on economic choice between remifentanil and food in squirrel monkeys - Alishan S. Amirali; Jacquelin C. Hecker; Hector L. Figueroa-Monsanto; Devin P. Effinger; Rodrigo A. Montoro; Hank P. Jedema; Caleb D. Vogt; Amy Hauck Newman; Charles W. Schindler; Charles W. Bradberry (Addiction Neuroscience, 2023)
We recently reported an economic choice task in which squirrel monkeys chose between differing amounts of remifentanil, a fast-acting opioid, or a food reward to develop a preclinical screen for evaluating potential pharmacotherapies for opioid dependence. Herein, two known opioid addiction treatments were evaluated using this task, as well as a potential new agent, cariprazine, a dopamine D2/D3 receptor partial agonist currently used to treat bipolar disorder and schizophrenia. Preclinical rodent studies suggest this class of compounds may reduce opioid self-administration. Squirrel monkeys were pretreated daily with clinically relevant doses of each compound during the five days of treatment evaluation using the economic choice task. Shifts in drug preference were measured as changes in subjects’ indifference values, where the probability of drug and milk choice are equivalent. Buprenorphine produced a significant shift in indifference value between baseline and treatment weeks, indicating a decrease in drug preference. Subjects treated with methadone and cariprazine did not show any significant shift in drug preference. Differences between the buprenorphine and methadone results likely reflect a lack of opioid dependence in the subjects. The cariprazine results suggest that it does not alter opioid reward in non-dependent primates over a five day period.